Mapping the Aveiro sea outfall plume: sampling strategy for an autonomous underwater vehicle - Patrícia Ramos (2002)
Near field model predictions can be used to reduce the uncertainty about outfall sewage plume location during amonitoring mission.In this paper we present an innovative methodology that uses these models to predict the plume location,establishing a sensing strategy applicable to a monitoring mission using an AUV.The paper describes two applications that implement this methodology, accomplishing the automatic missiondefinition using real-time oceanographic data.An AUV mission was conducted to detect and map the Aveiro outfall plume, making use of these applications tospecify an efficient sampling strategy.